Aristotle's Theory of the Unity of Science - Wilson, Malcolm, 1961- (Book collections on Project MUSE., 2000)
"Aristotle was the first philosopher to provide a theory of autonomous scientific disciplines and the systematic connections between those disciplines. This book presents the first comprehensive treatment of these systematic connections: analogy, focality, and cumulation." "Wilson appeals to these systematic connections in order to reconcile Aristotle's narrow theory of the subject-genus (described in the Posterior Analytics in terms of essential definitional connections among terms) with the more expansive conception found in Aristotle's scientific practice. These connections, all variations on the notion of abstraction, allow for the more expansive subject-genus, and in turn are based on concepts fundamental to the Posterior Analytics. Wilson thus treats the connections in their relation to Aristotle's theory of science and shows how they arise from his doctrine of abstraction. The effect of the argument is to place the connections, which are traditionally viewed as marginal, at the centre of Aristotle's theory of science." "The scholarly work of the last decade has argued that the Posterior Analytics is essential for an understanding of Aristotle's scientific practice. Wilson's book, while grounded in this research, extends its discoveries to the problems of the conditions for the unity of scientific disciplines."--Jacket.